Leadership in the Perspective of Fiqh Siyasah and Its Relevance to the Indonesian Constitutional System - Rawie Ikramul Fasya; Sayyid Ahmad Jiddan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to analyze in depth the principles of leadership from the perspective of Fiqh Siyasah and to examine their relevance to strengthening the constitutional system in Indonesia. Following the massive leadership transition after the 2024 General Election, Indonesia has faced major challenges related to the integrity of governmental governance, as reflected in the stagnation of the Corruption Perceptions Index (CPI) score at 34. This study employed a normative juridical legal research method with a philosophical approach to analyze secondary data derived from primary, secondary, and tertiary legal materials. The findings reveal that Fiqh Siyasah Dusturiyah conceptualizes leadership not merely as political power, but also as a theological and sociological mandate aimed at safeguarding religious values and managing public welfare. The classical criteria of Islamic leadership Amanah (trustworthiness), Shiddiq (truthfulness), and Fathanah (wisdom/intelligence) directly intersect with the demands of modern bureaucracy, such as accountability, transparency, and the merit system. Furthermore, within the framework of the Unitary State of the Republic of Indonesia (NKRI), Fiqh Siyasah regards Pancasila and the 1945 Constitution as legitimate national agreements (al-mitsaq al-wathani). The integration of Islamic political values is not realized through the formalization of a particular state form, but rather through the functional absorption of substantial ethical values into constitutional practices and public policies. In this way, it contributes to reducing the ideological dichotomy between religion and nationalism in order to create a more inclusive system of governance.